Molecular Mechanisms of Short-Term Plasticity: Role of Synapsin Phosphorylation in Augmentation and Potentiation of Spontaneous Glutamate Release - Cheng, Qing; Song, Sang-Ho; Augustine, George J. (Frontiers in Synaptic Neuroscience, 2018)
We used genetic and pharmacological approaches to identify the signaling pathways involved in augmentation and potentiation, two forms of activity dependent, short-term synaptic plasticity that enhance neurotransmitter release. Trains of presynaptic action potentials produced a robust increase in the frequency of miniature excitatory postsynaptic currents (mEPSCs). Following the end of the stimulus, mEPSC frequency followed a bi-exponential decay back to basal levels. The time constants of decay identified these two exponential components as the decay of augmentation and potentiation, respectively. Augmentation increased mEPSC frequency by 9.3-fold, while potentiation increased mEPSC frequency by 2.4-fold. In synapsin triple-knockout (TKO) neurons, augmentation was reduced by 83% and potentiation was reduced by 74%, suggesting that synapsins are key signaling elements in both forms of plasticity. To examine the synapsin isoforms involved, we expressed individual synapsin isoforms in TKO neurons. Synapsin IIIa was most effective in rescuing both augmentation and potentiation, while synapsin IIa was slightly less effective and synapsins Ia, Ib and IIb did not rescue. To determine the involvement of protein kinases in these two forms of short-term plasticity, we examined the effects of inhibitors of protein kinases A and C. While inhibition of PKC had little effect, PKA inhibition reduced augmentation by 76% and potentiation by 60%. Further, elevation of intracellular cAMP concentration, by either forskolin or IBMX, greatly increased mEPSC frequency and occluded the amount of augmentation and potentiation evoked by electrical stimulation. Finally, mutating a PKA phosphorylation site to non-phosphorylatable alanine abolished the ability of either synapsin IIa or IIIa to rescue both augmentation and potentiation. Together, these results indicate that PKA activation is required for both augmentation and potentiation of spontaneous neurotransmitter release. We conclude that PKA-mediated phosphorylation of synapsins – specifically either the synapsin IIa or IIIa isoforms - underlies both forms of presynaptic short-term plasticity.